Exterior building enclosures design process and composition for innovative facades - Boswell, C. Keith (Hoboken, New Jersey Wiley, 2013)
"Focused on the design process for architects and related professionals, this is a guide to the design and execution of sophisticated exterior building enclosures for a number of commercial building types and in a variety of building materials. Written by the technical director of the San Francisco office of the esteemed architecture firm Skidmore, Owings and Merrill (SOM), this book has a distinct focus on the design process by delineating the participants (architects, engineers, consultants) and their roles and responsibilities through collaboration, and tracking the design process through construction"--Provided by publisher.
Keywords: Exterior walls; Buildings -- Protection; Architectural design